Misperceived social norms and willingness to act against climate change - Peter Andre; Teodora Boneva; Felix Chopra; Armin Falk (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
We document the individual willingness to act against climate change and study the role of social norms in a large sample of US adults. Individual beliefs about social norms positively predict pro-climate donations, comparable in strength to universal moral values and economic preferences such as patience and reciprocity. However, we document systematic misperceptions of social norms. Respondents vastly underestimate the prevalence of climate-friendly behaviors and norms. Correcting these misperceptions in an experiment causally raises individual willingness to act against climate change as well as individual support for climate policies. The effects are strongest for individuals who are skeptical about the existence and threat of global warming.
Keywords: D64; D83; D91; Q51; Q54; Z13; 330; Climate change; climate behavior; climate policies; social norms; misperception; beliefs; economic preferences; moral values; survey experiments